Determination of carbon monoxide using a coated quartz crystal sensor - Guimarães, Orliney Maciel; Zaniquelli, Maria Elisabete Darbello; Castro, Jorge Ricardo Moreira; Balbo, Valdir Roberto; de Andrade, José Fernando (Eclética Química, 2006)
Carbon monoxide was detected and determined by a piezoelectric quartz crystal sensor coated with nickel(II)-phthalocyanine 50 % (v/v) solution in glycerine. Studies on the effect of temperature, flow rate, and some possible interferents were carried out. Calibration curves, sensor stability (lifetime) and the precision of measurements were also verified. The resulting selectivity is probably due to the coordinative binding between the electronically unsatured metal complexes and the analyte. The analytical curve is linear in the concentration range 0.10 to 1.0 % (v/v).